Comparative Analysis of Legal Policies Regarding Force Major During Covid-19 Pandemic in Indonesia and China - Dolot Al Hasni Bakung; Mohamad Hidayat Muhtar; Nabih Amer (Faculty of Law, Universitas Pattimura, 2022)
Covid-19 as a pandemic in the 20th century has brought consequences in many aspects, one of which is the force major aspect. The force majeure policy in Indonesia is still incomplete, unlike China, which already has a more complete policy. The purpose of the research is to be able to find out about the Covid-19 policy in Indonesia and to compare the Indonesian and Chinese force major policy settings. The research method uses a normative research type with a statutory approach. The results of the study show that Indonesia's policy in dealing with covid 19 has problems in two policies, namely: the provision of information and the Lockdown policy. Meanwhile, the comparison problem with China is better by providing a mechanism with more legal certainty, namely providing access to the determination of force major against the Supreme Court, while Indonesia does not have a similar mechanism.